Planejamento do meio físico a partir de uma abordagem da técnica de capacidade de uso da terra na sub-bacia dso Rio das Pedras - Itatinga - SP - Pisani, Rodrigo José [UNESP]; Demarchi, Júlio César [UNESP]; Campos, Sergio [UNESP]; Barros, Zacarias Xavier de [UNESP] (My University, 2013)
The study aimed mapping of the land use capacity classes for the Rio das Pedras watershed, Itatinga-SP in order to provide another mechanism of environmental planning for the studied area. It was used 1:10,000 topographic letters for the slope map generation which was overlaid with the studied area soil map. It was applied the judgment table criteria method, for generation of land use capacity map of the studied area. It were identified the following results: First, class III with constraints in relation of low fertility and restrictions about erosion risks on high slope areas. Second, class VI with the same characteristics of class III however with the presence of an aggravating factor of sand texture in all horizons, resulting in high risks of erosion events, especially in high slopes areas, and contamination by pollutants due the high soil permeability. Conclusions: It was verified that the more critical regions for land use capacity classes were VIs and mainly VIes class. The last one has more high relief areas and the presence of Neossolo Quartzarenico soil, with a big erosion propensity. The land use capacity map allow making different decisions for each region of the watershed respecting their individual characteristics.

O estudo visou o mapeamento das classes de capacidade de uso da terra para a subbacia do Rio das Pedras, Itatinga-SP a fim de se prover mais um mecanismo de planejamento do meio físico para a área estudada. Foram utilizadas cartas topográficas na escala 1:10.000 para a obtenção do mapa de declividade, o qual foi posteriormente cruzado com o mapa de solos da área. Foi aplicado o método de critério do quadro de julgamento, para a geração do mapa de capacidade de uso da área estudada. Foram identificados os seguintes resultados: Primeiro, classe III com limitações quanto à baixa fertilidade aparente e restrições quanto ao risco de erosão nas áreas de declive mais acentuadas. Segundo, classe VI com as mesmas características da classe III, porém com o agravante de textura arenosa em todo perfil, implicando maiores riscos de erosão especialmente em áreas de declive mais acentuado e contaminação de poluentes por apresentar alta permeabilidade. Conclusões: Foi verificado que as regiões mais críticas para capacidade de uso foram as classes VIs e principalmente a classe VIes. Esta ultima por possuir as áreas mais declivosas e da presença dos Neossolos Quartzarênicos, com grande propensão a erosão. O mapa de capacidade de uso da terra permite a tomada de diferentes decisões para cada região da sub-bacia respeitando suas características individuais.
Environmental planning by aproaching of land use capacity tequinique for the Rio das Pedras watershed, Itatinga-SP
Keywords: Environmental planning; Erosion risk; Slope; Planejamento ambiental; Risco de erosão; Declividade